Caring for family caregivers: An analysis of a family-centered intervention - Carme Ferré-Grau; Maria Sevilla Casado; Dolors Cid-Buera; Mar LLeixà-Fortuño; Pilar Monteso-Curto; Marta Berenguer-Poblet
Objective To assess the effectiveness of Problem-Solving Therapy (PST) on family caregivers through the use of scales to measure anxiety, depression and emotional distress; and to explore facilitating factors and obstacles for its use based on the narrative of nurses. Method A clinical trial and an exploratory focus group with the use of mixed analysis methodology. The study was conducted in a primary health care center in Tarragona, Spain, and the sample consisted of 122 family caregivers who were included in the home care service, and 10 nurses who participated in the intervention group. Family caregivers with evident symptoms of anxiety, depression and emotional distress received PST in the intervention group. The intervention group also consisted of a discussion with eight nurses, which was transcribed and submitted to content analysis. Conclusion Problem-Solving Therapy proved to be effective in reducing perceived anxiety, depression and emotional distress. We identified its strong points and obstacles as described by nurses.